PEMBERDAYAAN PEMUDA MIDANG MELALUI PEMANFAATAN PINGGIR KALI SEBAGAI WARUNG HIDUP WARGA DUSUN MIDANG, LOMBOK BARAT - Afifah Farida Jufri; Jufri, Afifah Farida; Nawawi, Ahmad; Iemaaniah, Zuhdiyah Matienatul (Jurnal Pepadu, 2024)
The very dense settlement of Midang Hamlet leaves a narrow area of ​​land along the edge of the irrigation canal, which is more often referred to by residents as Kali Midang. This narrow land has the potential to meet food needs, improve community nutrition, source plant diversity and create an optimal living environment around the household. The potential of this narrow land can be utilized by optimizing the cultivation of a variety of plants by forming a living stall. The aim of this service activity is; 1) utilize the narrow land at the edge of the river to become a food stall for residents to support food security, and 2) increase the knowledge of the community, especially the youth of Midang hamlet, about plant cultivation techniques on limited land. The method used in this service activity is the participatory action method where Midang youth are directly involved in each activity. The stages in this activity start from the preparation, implementation and evaluation stages. The Midang Hijau movement which was carried out in Midang Hamlet RT 02 ran smoothly and had a positive impact on the residents. Residents are quite interested and enthusiastic in participating in every activity process. Midang Hijau is a trigger for the residents of Midang Hamlet to utilize small land, not only land on the edge of the river but also at home or in other small areas of land that have not been utilized optimally by planting vegetables and kitchen spices for daily needs so that residents can create a living stall. to support daily kitchen needs.